2015
DOI: 10.1055/s-0035-1545918
|View full text |Cite
|
Sign up to set email alerts
|

Operative Therapy for Heterotopic Scar Pregnancy and Successful Birth of the Intrauterine Foetus – Case Report and Review of the Literature

Abstract: A heterotopic pregnancy in the vicinity of a previous Caesarean section scar (HSP) occurs frequently after fertility treatment. In spite of the low incidence to date, the increasing numbers of Caesarean sections as well as IVF treatment will probably lead to a higher prevalence in the future. Up to now the literature contains only isolated case reports on therapeutic options. These range from conservative management through selective termination of the HSP by injections of methotrexate or potassium chloride in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Therefore, in the present study, we conducted a search and review of the literature pertaining to HCSP. To the best of our knowledge, a total of 23 cases of HCSP have been reported in the English literature [2, 4, 10, 1226], and the results are summarized in Additional file 1: Table S1. The reported treatments included conservative management, fetal reduction by potassium chloride, laparoscopic excision, aspiration of embryonic or ectopic gestational sac, hysteroscopy with directed evacuation, injection of a mixture of MTX and KCl, or laparotomic excision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the present study, we conducted a search and review of the literature pertaining to HCSP. To the best of our knowledge, a total of 23 cases of HCSP have been reported in the English literature [2, 4, 10, 1226], and the results are summarized in Additional file 1: Table S1. The reported treatments included conservative management, fetal reduction by potassium chloride, laparoscopic excision, aspiration of embryonic or ectopic gestational sac, hysteroscopy with directed evacuation, injection of a mixture of MTX and KCl, or laparotomic excision.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported hysteroscopic management of heterotopic cesarean scar pregnancy under ultrasound guidance at 7 weeks of gestation, with the baby delivered at 39 weeks of pregnancy [17]. Armbrust et al successfully excised a HSP by laparotomy at 7 weeks of gestation, with a subsequent uncomplicated cesarean section and delivery of a healthy baby at 37 weeks of pregnancy [26]. …”
Section: Discussionmentioning
confidence: 99%
“…The extrauterine pregnancy may be located in the fallopian tube, cervix, caesarean section scar. The latter one is expected to increase alongside with the increasing rate of caesarean sections [56,57].…”
Section: Heterotopic Pregnancymentioning
confidence: 99%
“…However, morbidly adherent placenta and massive bleeding during ongoing pregnancy are common obstetric complications[ 5 , 9 ]. Surgical management has been preferred by some authors[ 6 , 10 , 11 ]. Because of the rarity of HCSP, no universal treatment guidelines have been established when IUP is desired to be preserved.…”
Section: Introductionmentioning
confidence: 99%